EFFICACY OF AYURVEDIC MODALITIES IN CHRONIC PELVIC INFLAMMATION - A CASE STUDY - Dr. Manjusha Karkare, Dr. Dhanashree Deshpande, Dr. Shriniwas Jadhav, (International Journal of Modern Agriculture, 2021)
In present era the women walk shoulder to shoulder with men, but since time immemorial women have always been a step ahead of men when it comes to tolerating pain. Chronic pelvic inflammation is a common complaint in gynecology patients. It is a spectrum of infection and inflammation of the upper genital tract organs typically involving the uterus (endometrium), fallopian tubes, ovaries, pelvic peritoneum and surrounding structures. A patient’s signs and symptoms suggestive of KaphaVatajyonidushti presented in the PrasutiTantraevumStreeRoga (OBG)OPD of Parul Ayurveda Hospital, Vadodara,Gujarat. She was treated with oral medication and Sthanika(local) Karma i.e. Yoni prakshalan and Yonidhoopana. Yonidhoopana is practical procedure in which fumigation of vagina is performed by using herbal medicines in smoke form. Yonidhoopana is a part of regular SutikaParicharya in Indian culture but it is not so widely used in gynecology patients. The encouraging results of this case of Yonidhoopana will help us to select this therapy for patients with similar complaints in the future.